Thermal stability of end‐capped and linear sulfonated polyimides, sulfonated polystyrene, and Nafion 117. Issue 3 (2nd September 2017) - Gong, Chenliang; Pinatti, Laura; Lavigne, Gary; Shaw, Montgomery T.; Scola, Daniel A.
ABSTRACT: The thermal stability of end‐caped and linear sulfonated polyimides (SPIs), sulfonated polystyrene (SPS), and a sulfonated perfluorinated hydrocarbon, Nafion 117, and the corresponding triethylammonium sulfonate salts was investigated by dynamic and isothermal thermogravimetric analysis (TGA). Gas chromatographic‐mass spectrographic analysis (GC/MS) of the sulfonated polymers and the salts to determine the volatiles released from acid and salt groups over a temperature range 200–275 °C was also investigated. GC/MS analysis reveals that water and sulfur dioxide volatiles are released from the sulfonic acids and water, sulfur dioxide and triethyl amine are released from the sulfonate salts. Dynamic and isothermal TGA studies based on weight loss revealed that the SPIs exhibited superior thermal stability than SPS and Nafion 117 sulfonic acids. However, dynamic TGA curves to determine the onset decomposition temperature of the sulfonic acid group reveal that Nafion 117 and SPS sulfonic acids exhibited greater thermal stabilities than the SPIs. The mechanisms of sulfonic acid and triethylammonium sulfonate salt decompositions based on GC/MS, 13 C‐NMR, and dynamic TGA curves are proposed. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45694. Abstract :